65 Nurse led radial access for coronary angiography. (May 2019) - Wojcik, Dorota; Manmathan, Gavin; Ahmad, Mahmood; Candilio, Luciano; Patel, Niket; Patel, Deven; Coghlan, Gerry; Lockie, Timothy; Rakhit, Roby
Abstract : Introduction: NHS England announced a new nurse angiographer role with the purpose of reducing hospital waiting lists for elective angiography. Methods: Development of a standardised operating procedure for training in Radial Arterial Access (RAA), guidance on how to minimise the risk and recognise complications and post procedural limb management. Obtaining approval at the new procedures committee. Training program 50 consultant supervised nurse led procedures for (RAA), establishing expertise in 100 further procedures, followed by roll out of the program to other nursing staff. Results: During training (RAA) cannulation was successful on 1st attempt in 42 out of 50 (success rate allowing for two attempts 84%), with no complications recorded. Successful access by a more experienced operator N = 7, failed (RAA) N = 1. The following 100 were performed independently on unselected patients (success rate 81%; (1st pass 70)), with no complications, need for alternate access routes, N = 1. The following table details the success rate and patient comfort score recorded during 104 procedures performed by a nurse specialist and trainee registrars. Conclusion: Nurse-led (RAA) is safe and feasible and has the potential to improve catheter laboratory efficiency, patient satisfaction, standardise procedure training and improve staff retention. Our next steps will be to train more nurses in radial access and progress to nurse led angiography. Conflict of Interest: None